Cost, Time and Pavement Alternatives Analysis of Technical and Costs - Budiyanto, Arief; Muhammadun, Haris; Marleno, Risma (CV. Proaksara Global Transeduka, 2024)
The research on the Teuku Umar Road - Rajawali Road Preservation project aims to find out the technical calculations, costs and time so that a more efficient alternative can be chosen. The calculation analysis on Rigid Pavement and Flexible Pavement uses the Road Pavement Design Manual Method No. 02 / M / BM / 2017 with a 20-year plan life. In the calculation of the AHSP cost analysis of the Highways Sector in accordance with Permen PUPR No. 8 of 2023. Periodic maintenance costs for rigid pavement are 6% and routine maintenance costs on flexible pavement are 2% while periodic maintenance costs are 8% of the initial budget. The results of this research analysis show the cost of rigid pavement is Rp. 11,349,200,000 and the implementation time is 120 calendar days. While the cost of flexible pavement is Rp. 8,414,500,000 and the implementation time is 95 calendar days. The results of the calculation of choosing a more efficient alternative based on the calculation of Capitalized Cost show that rigid pavement in terms of cost is smaller than flexible pavement, so rigid pavement alternatives are chosen.